Modification of The Front Kick Accuracy for Pencak Silat Novice Athletes (Media Ilmu Keolahragaan Indonesia, 2022)
The purpose of this study was to create a media for front kick accuracy in Pencak silat athletes. This type of this study is research and development (RD) with descriptive data analysis techniques using percentages. The instrument used was a questionnaire. The result of this research is a modified front kick precision tool. This study found that the expert validation data is 98.75% in the "Very Good" category. The overall small trial data is 80% in the "Good" category. In the extensive trial, the overall was 88% in the "Very Good" category. The conclusion of the front kick product assessment tool is particularly Good for front kick accuracy training for beginner and professional athletes. In further research, it is necessary to develop the material for the tool.